Resilience and Performance of Prefabricated Modular Buildings Against Natural Disasters - Thusitha Ginigaddara; Chathushika Ekanayake; Tharaka Gunawardena; Priyan Mendis (Electronic Journal of Structural Engineering, 2023)
Earliest global movement towards modular construction originated as a solution to the sudden housing demand which occurred during events such as British colonization, the California gold rush, the world wars and post war settlement. Present day, modular construction is explored by researchers aiming to maximize from the benefits of Industry 4.0 technology. Buildings of the 21st century frequently face natural disasters such as earthquakes, pandemics, floods, cyclones, and bushfires. This review is developed around recent episodes such as the Covid-19 pandemic which demands design resilience and the intraplate earthquake of Australia, which stresses on the necessity of improved structural performance of modular buildings. To understand the performance of modular buildings against natural disasters, this paper critically reviews recent developments in modular construction research and applications. Through the extensive analysis of literature, this paper identifies future research domains of modular construction that are required to confront natural disasters. The outcomes of this review facilitate timely and sustainable research directives towards resilient modular buildings.